Coping with cyberbullying strategies from the victim’s perspective in Mexican adolescent Junior and High School students - Sandoval Martínez, Josefina; Luna Bernal, Alejandro César Antonio; De Gante Casas, Alejandra (IE Revista de Investigación Educativa de la REDIECH, 2021)
The Coping with Cyberbullying Strategies from the Victim’s perspective Inventory (Inventario de Estrategias de Afrontamiento del Ciberacoso desde la perspectiva de la Víctima, IEAC-V) is an instrument that measures the degree to which adolescents tend to use seven types of strategies to deal with possible cyberbullying situations, in the event of becoming victims: aggressive strategies, reporting, ignoring and deflecting concern, seeking support, gather evidence, avoid the bully, and to stop using social networks or the internet. The present paper provides new relevant information about the validity of this instrument through a confirmatory factor analysis. The sample was composed of 992 adolescent Junior and High School students, aged 12 to 20 years. The results showed factor loadings, coefficients of determination and adjustment values adequate. There were also adequate reliability indices as well as statistically significant differences by gender, and school grade. These and other results are discussed in the context of the psychological literature on coping with cyberbullying strategies in adolescence.